2017
DOI: 10.1371/journal.pone.0171442
|View full text |Cite
|
Sign up to set email alerts
|

DNMT 1 maintains hypermethylation of CAG promoter specific region and prevents expression of exogenous gene in fat-1 transgenic sheep

Abstract: Methylation is an important issue in gene expression regulation and also in the fields of genetics and reproduction. In this study, we created fat-1 transgenic sheep, investigated the fine-mapping and the modulatory mechanisms of promoter methylation. Sheep fetal fibroblasts were transfected by pCAG-fat1-IRES-EGFP. Monoclonal cell line was screened as nuclear donor and carried out nuclear transfer (441 transgenic cloned embryos, 52 synchronism recipient sheep). Six offsprings were obtained. Expressions of exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…The introduction of the Fat-1 gene in mouse, pig, sheep, cattle, and cow resulted in high levels of n-3 PUFAs and significantly lower n-6/n-3 PUFA ratios in their tissues [10][11][12]23,46,47]. In our study, the same results were obtained by comparing n-6 and n-3 PUFA contents between 100-day transgenic fetuses and wild type fetuses.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The introduction of the Fat-1 gene in mouse, pig, sheep, cattle, and cow resulted in high levels of n-3 PUFAs and significantly lower n-6/n-3 PUFA ratios in their tissues [10][11][12]23,46,47]. In our study, the same results were obtained by comparing n-6 and n-3 PUFA contents between 100-day transgenic fetuses and wild type fetuses.…”
Section: Discussionsupporting
confidence: 81%
“…However, the transgenic fetuses possessed both Fat-1 expressing and silencing cells in their tissues. Our previous study indicated that the hypermethylation status in the specific CAG promoter region may be responsible for preventing Fat-1 expression in transgenic-silencing cells [23]. In the current study, the skin cells with or without Fat-1 expression were further compared at the transcriptome level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Danio rerio fat1 oraz fat1/fat2 [37] szczur fat-1 [38] owca fat-1 [39] świnia hfat-1 [40] sFat-1 [41] krowa fat-1 [42] skrzyżowanie ze sobą dwóch heterozygotycznych myszy: fat-1 i fat-2 otrzymano myszy fat-1/fat-2 zwane myszami "Omega". Dzięki temu możliwym stała się synteza kwasów omega-6 i omega-3 przez ssaki z innych niż WNKT składników diety tzn.…”
Section: Zwierzęunclassified
“…Transgene has been the considerable controversy all around the world. In terms of fat-1 transgenic animals, the expression of exogenous gene fat-1 can be detected in tissues and upregulates omega-3 polyunsaturated fatty acid (n-3 PUFA) (Yang et al 2017). N-3 PUFAs, as essential fatty acids, cannot be synthesized in mammals (van West and Maes 2003).…”
Section: Introductionmentioning
confidence: 99%